Implementasi Kegiatan Baca Tulis Al-Qur’an Dalam Menumbuhkan Karakter Qur’ani Pada Diri Peserta Didik - Hasby Izhari Nur; Amirudin, Noor (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2025)
The Qur’an Reading and Writing (BTQ) program serves as a strategic approach to cultivating Qur’anic character within the Islamic education system. The implementation of this program is essential for integrating Qur’anic literacy skills with moral values such as honesty, responsibility, and discipline. This study aims to analyze the implementation of BTQ activities in fostering Qur’anic character among students at SMP Muhammadiyah 4 Kebomas Gresik. A descriptive qualitative method was employed, utilizing data collection techniques including observation, interviews, and documentation. The results indicate that BTQ is conducted regularly with the support of competent teachers, effective learning media, and a contextual value-based approach. Despite several obstacles such as limited instructional time and low student motivation, the program positively contributes to the gradual development of Qur’anic behavior. Therefore, BTQ offers a significant contribution to Islamic educational practices that emphasize value-driven and character-based learning